On the Moral Geography of Cities: Three Singapore Hostess Bars in a Suburban ‘High Street’ Setting - James , Kieran Edmond; Awan , Faizah; Walsh , Rex John (Recent Research Advances in Arts and Social Studies Vol. 5, 2024)
Singapore’s business model has been to rely upon foreign capital from the Global North and foreign labour, from the less-developed countries of the region, so as to maximize surplus value. The Singapore ‘business model’ has remained essentially unchanged since the foundation of modern Singapore by Sir Thomas Stamford Raffles in 1819. We study three hostess pubs on Joo Chiat Road, Singapore - a ‘Vietnam pub’ and two ‘Filipina pubs’, utilizing the concept of ‘assemblages’ based on Bøhling’s work on Copenhagen nightlife. We compare and contrast the customer demographics of each night-time economy (NTE) establishment, and the resultant culture, which is a product of the race/ethnicity of the hostesses, the race/ethnicity and ages of the patrons, the policies and ethos of the owner/manager, and the pricing model whereby hostesses get financially rewarded. At the beginning of 2018, I decided to embark on the research project formally. I had come to perceive that the cultures and dominant practices at the Vietnamese pubs and the two Filipina pubs on Joo Chiat Road were significantly different and that this point was worthy of further investigation and commentary. The Filipina pubs rely upon ‘ladies’ drinks’ whereas the Vietnam pub fosters a tipping system. Whilst the ladies’ drinks model suggests a hyper-capitalist business setting, the tipping model remains feudal, honour-based and debt-based. These observations derive from Marx’s Historical Materialism Theory where remnants of feudal or pre-capitalist practices linger on into the capitalist modern era.